Global burden of anemia and cause among children under five years 1990–2019: findings from the global burden of disease study 2019 - Liu, Yujuan; Ren, Weifang; Wang, Shuying; Xiang, Minmin; Zhang, Shunxian; Zhang, Feng (Frontiers in Nutrition, 2024)
Background Anemia represents a significant global health issue affecting numerous children and women, characterized by diminished hemoglobin levels that may impede cognitive and developmental progress. Although commonly attributed to iron deficiency, the etiology of anemia in this demographic is multifaceted, encompassing nutritional, genetic, and infectious contributors. Nonetheless, there is a lack of high-quality data on anemia prevalence and causes analysis among children under 5 years. The aim of this study was to provide a comprehensive global assessment of the burden of anemia and its causes among children under 5 years, using data from the Global Burden of Disease Study 2019. Methods This investigation utilized data from the Global Burden of Disease Study (GBD) 2019 to assess the prevalence and years lived with disability (YLD) attributable to anemia in children under five from 1990 to 2019. Analyses were conducted to delineate age-specific YLD, prevalence rates, and etiological factors, with stratification by gender and Socio-Demographic Index (SDI). Results In 2019, anemia imposed a substantial global burden on children under five, with a reported YLD of 1,252.88 (95% UI: 831.62–1,831.34) per 100,000 population. The prevalence of moderate anemia was highest at 985.46 (95% UI: 646.24–1,450.49) per 100,000, surpassing both severe anemia at 197.82 (95% UI: 132.53–277.80) per 100,000 and mild anemia at 69.59 (95% UI: 24.62–152.53) per 100,000. Globally, the total prevalence was 39,517.75 (95% UI: 38,784.81 - 40,239.62) cases per 100,000 population. Notably, disparities were evident between genders, with males demonstrating higher YLD and prevalence rates than females. Iron deficiency emerged as the leading cause globally, with significant contributions from hemoglobinopathies and other nutritional deficiencies. Regions with a low Socio-Demographic Index, particularly sub-Saharan Africa and South Asia, exhibited the most pronounced burdens. Despite a declining trend over three decades, persistent regional and gender-based disparities highlight the necessity for continuous and focused public health interventions. Conclusion The burden of anemia among children under five continues to be considerable, marked by stark regional and socioeconomic disparities. These findings underscore the urgent need for advanced nutritional and healthcare strategies tailored to alleviate anemia in this vulnerable population, with a particular emphasis on regions exhibiting low SDIs. The sustained prevalence of high anemia rates in these areas underscores the imperative for persistent, localized intervention efforts.